1993
DOI: 10.2134/agronj1993.00021962008500030042x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Selection for Yield and Stability in Crop Performance Trials: Consequences for Growers

Abstract: Utilization of genotype x environment (GE) interadion encountered in crop performance trials is an important issue among plant breeders and agronomists. Practical integration of yield and stability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
272
0
30

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(305 citation statements)
references
References 7 publications
3
272
0
30
Order By: Relevance
“…Previous studies (Kang andPham 1991, Kang 1993) showed that simultaneous selection for yield and stability reduced type II errors and benefited growers. Although growers may not evaluate such scenarios at the farm, researchers can present possible options from such studies to provide guidance to growers on variety choice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Kang andPham 1991, Kang 1993) showed that simultaneous selection for yield and stability reduced type II errors and benefited growers. Although growers may not evaluate such scenarios at the farm, researchers can present possible options from such studies to provide guidance to growers on variety choice.…”
Section: Discussionmentioning
confidence: 99%
“…This ASV is comparable with the methods used by Shukla, Eberhart, and Russell for genotype stability (Purchase et al, 2000). The development and use of the yield-stability statistic (YSi) was also used to recommend varieties (Kang, 1993;Pazdernik et al, 1997). Kang (1993) proposed an improved superior stability index (I) that is free from all the aforesaid drawbacks (Rao and Prabhakaran, 2005).…”
Section: Introductionmentioning
confidence: 93%
“…By using these measures, suitable rice varieties can be identified for varying existing environmental conditions. Stability per se should however not be the only selection parameter because the most stable genotypes would not necessarily give the best yield performance (Mohammadi et al, 2007;Mohammadi and Amri, 2008); hence, there is a need for approaches that incorporate both mean yield and stability in a single index and that is why various authors have introduced different selection criteria for simultaneous selection of yield and stability (Eskridge, 1990;Kang, 1993;Dashiell et al, 1994;Bajpai and Prabhakaran, 2000;Rao and Prabhakaran, 2005;Farshadfar, 2008;Babarmanzoor et al, 2009). In this regard, since ASV takes into account both IPCA1 and IPCA2, most of the variation in the GE interaction is justified; therefore, the rank of ASV and yield mean is such that the lowest ASV is rank one, while the highest yield mean is rank one and the ranks are then summed in a single simultaneous selection index of yield and yield stability called the yield stability index (YSI).…”
Section: Yield Stability Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerosos métodos basados en diferentes principios matemáticos-estadísticos, han sido descritos y utilizados para la evaluación de la interacción genotipo por ambiente, estos permiten determinar la estabilidad y adaptabilidad fenotípica de los cultivares cuando son evaluados en diferentes localidades y años. Entre los más conocidos se pueden citar : Finlay y Wilkinson (1963), Eberhart y Russell (1966), Baker (1988), Zobel et al (1988), Lin y Binns (1988), Cruz et al (1989), Kang (1993), Yan et al (2000).…”
Section: Introductionunclassified